Integrative Analyses of Circulating mRNA and lncRNA Expression Profile in Plasma of Lung Cancer Patients - Li, Haoran; Li, Mingru; Guo, Haifa; Lin, Guihu; Huang, Qi; Qiu, Mantang (Frontiers in Oncology, 2022)
Circulating free RNA (cfRNA) have been regarded as potential biomarkers for “liquid biopsy” in cancers. But the circulating mRNA and long noncoding RNA (lncRNA) profiles lung cancer have not been fully characterized. In this study, we profiled circulating mRNA and lncRNA profile of 16 lung cancer patients (11 adenocarcinoma, 3 squamous carcinoma, and 2 small cell cancer) and 4 patients with benign pulmonary nodules. Compared with benign pulmonary nodules, 807 mRNAs and 1763 lncRNAs were differentially expressed in plasma of lung adenocarcinoma patients. For lung squamous carcinoma, 256 mRNAs and 946 lncRNAs were differentially expressed. And 231 mRNAs and 298 lncRNAs were differentially expressed in small cell lung cancer. Eleven mRNAs, 51 lncRNAs and 207 canonical pathways were differentially expressed in lung cancer in total. MYC, a transcription regulator associated with the stemness of cancer cells, is overexpressed in lung adenocarcinoma. TGFB1, which plays pleiotropic roles in cancer progression, was found upregulated in lung squamous carcinoma. MALAT1, a well-known oncogenic lncRNA, was also found upregulated in lung squamous carcinoma. Thus, this study provided a systematic resource of mRNA and lncRNA expression profile in lung cancer plasma.